Pengujian Gaya Kepemimpinan Organisasi - Yuyun Rachmayuniawati; Sri Mulyeni (Politeknik Ganesha Medan, 2020)
This research tries to test leadership style in organizations. The research directed to evaluate the sentences stated by the leaders which signify their leadership style. In this study we propose three types of leadership: transformational (), pseudo-transformational (), and laissez-faire leadership (). Then we examine what factors that make a leader transformational leader, pseudo-transformational, and or laissez-faire leader. We pose three variables as independent variables: satisfaction (), trust (), and respect (). Based on the result, in case of transformational leadership we find that only satisfaction that influences positive significant on leadership style. In case of laissez-faire leadership, only trust which can influence positive significant on leadership style. Meanwhile in the pseudo-transformational case, we do not find any variable that influences on leadership style. This finding confirms factor of followers that make leaders a leader: environment and circumtances.